KAJIAN PERBANDINGAN HAK WARISAN ANAK ANGKAT DI INDONESIA DAN MALAYSIA - Mohammad Ghozali; Muhammad Irkham Firdaus; Muhammad Aunurrochim Mas'ad Saleh; Zahari Mahad Musa (Malaysian Journal of Syariah and Law)
This study aims to analyze and compare the inheritance rights of adopted children in Indonesia and Malaysia while integrating them with the principles of Islamic inheritance law. The primary focus of this study is to examine the statutory status of inheritance rights of adopted children in relation to their adoptive parents, considering that both countries have a majority Muslim population. An adopted child is defined as an individual whose custody, education, and care are transferred from their biological family or legal guardian to adoptive parents. Although the status of adopted children is legally recognized in Malaysia and Indonesia, issues often arise concerning their inheritance rights from their adoptive parents' estates. This study employs a qualitative approach using descriptive, comparisons and doctrinal analysis to understand this position. From the perspective of Islamic law, adopted children do not have direct inheritance rights from their adoptive parents except through wasiat wajibah (compulsory bequest), which cannot exceed one-third of the total estate and hibah. Conversely, under several statues of law, the status of adopted children in certain cases is equated with that of biological children, enabling them to become heirs. The findings of this study are expected to provide guidance and legal considerations in resolving inheritance disputes, particularly those involving the inheritance rights of adopted children. In specific circumstances, adopted children may still be entitled to inheritance, provided that the bequest does not exceed one-third of the total estate, in alignment with the principles of wasiat wajibah under Islamic law.